Intergenerational consequences of migration : Socio-economic, Family and Cultural Patterns of Stability and Change in Turkey and Europe /: Socio-economic, Family and Cultural Patterns of Stability and Change in Turkey and Europe. (2015) - Guveli, Ayse; Ganzeboom, Harry; Platt, Lucinda; Nauck, Bernhard; Baykara-Krumme, Helen; Eroglu, Sebnem; Bayrakdar, Sait; Sözeri, Efe K; Spierings, Niels
No abstract available